Durability and thermal stability of ultra high-performance fibre-reinforced concrete (UHPFRC) incorporating calcined clay. Issue 5 (4th May 2017) - Rabehi, Bahia; Ghernouti, Youcef; Boumchedda, Khaled; Li, Alex; Drir, Abdelkader
Abstract : This work aims to investigate the effect of metakaolin represented by calcined clay of Djbel Debbagh quality 3 (DD) as a pozzolan addition on physical mechanical properties and the durability of Ultra-High Performance Fibre-Reinforced Concrete (UHPFRC), compared to the silica fume (SF). Within the scope of this study, durability tests, such as chloride penetration resistance of various mixtures of UHPFRC based on steel fibres, have been investigated besides mechanical properties. The comparison of thermal stability of these mixtures, with two other formulations based on SF and calcined clay DD with polypropylene fibers is studied. The experimental results showed that the substitution of SF by calcined clay DD, makes it possible to produce UHPFRC with equivalent mechanical performance and a good resistance to penetration of chloride ions, this calcined clay has a high pozzolanic reactivity and can be used as fireclay addition which contributes to improve thermal behaviour of concrete. The specimens containing polypropylene fibres exhibit a good thermal stability compared to those containing steel fibres.